Challenges and Opportunities in Teaching Hadith in the Digital Era: A Case Study of MTs Mahadurrokan Sekeladi - Amellia Putri Syahrani; Dinda Jumiati; Zarkasih (Global Action and Education for Society, 2025)
This research examines the challenges and opportunities in learning hadith in the digital era through a case study at MTs Mahadurrokan Sekeladi, Riau. Digital transformation has brought significant changes in the methods of teaching religious sciences, including hadith as the second source of Islamic law after the Qur'an. This study used a qualitative approach with an in-depth interview method with hadith teachers at the local school. The results of the study show that the digital era provides great opportunities in the accessibility of hadith sources, learning efficiency, and innovation in teaching methodologies. However, the main challenges include the validity of digital sources, the lack of digital literacy of teachers, and the risk of reduced personal interaction in traditional learning. This study recommends a planned integration of digital technologies while maintaining traditional values in hadith teaching.